Performance of hydrated lime-pond ash treated peat soil / Zeety Md. Yusof - Md. Yusof, Zeety (2018)
The economic slowdown in Malaysia has led many development projects to invade into peatlands, which is known as problematic ground. The behaviour of this ground to the loads required improvement to the soil structure in the hope that it can increase the bearing strength. This study was conducted to identify the peat soil bearing strength stabilised with hydrated lime and pond ash mixtures. The strength properties of different mixes of composition and soaking periods were also identified through laboratory tests and finite element simulations. Sixteen types of treated peat samples containing various hydrated lime and pond ash mixtures have been developed. These samples have been soaked in water for 10 soaking times ranging from 0 days to 150 days and tested for unconfined compressive strength respectively. Selected samples with good performance of strength were tested for permeability and consolidation. Further observations on the chemical content and microstructure of the treated peat were also being carried out. Based on the good mixture, the settlements of treated peat were simulated using finite element method. From this study, it is found that the treated peat with 20% pond ash with 12% hydrated lime with the longer soaking period gave the good strength. The evidence from scan electron microscope showed a good microstructure contributes to the strength. Effect of soaking is very significant to the hydrated lime-pond ash treated peat and can be prevailed from laboratory studies and finite element simulation. The scanning electron microscope shows the cementitious products have increased the pond ash-hydrated lime dosages and clogged the pore spaces. The optimal mix design resulted in maximum unconfined compressive strength contributed higher strength in 60 and 90 days soaking. The pozzolanic process blocking of the peat pores, reduces the permeability, increases the strength gain of the treated peat and decrease the compressibility of the treated peat. The analytical methods anticipate a less settlement than the finite element analyses.